Physical activity in adults from two Brazilian areas: similarities and differences - Pedro C. Hallal; Sandra M. Matsudo; Victor K. R. Matsudo; Timóteo L. Araújo; Douglas R. Andrade; Andréa D. Bertoldi
Lack of comparability has been a major limitation in studies on physical activity, due to the utilization of different methodological instruments and inconsistent cut-off points. This study aims to compare the levels of physical activity in adults from two Brazilian areas: (a) São Paulo, the richest State in the country; (b) Pelotas, a medium-sized southern Brazilian city. Both sites used cross-sectional population-based designs, with multiple-stage sampling strategies. Level of physical activity was assessed with the short version of the International Physical Activity Questionnaire. Prevalence of sedentary lifestyle was three times higher in Pelotas than in São Paulo. On the other hand, the proportion of very active subjects was significantly higher in Pelotas. The proportion of insufficiently active individuals (sedentary + irregularly active) was almost identical between the sites. Socioeconomic status was inversely related to level of physical activity in both sites. Among the insufficiently active subjects, those living in São Paulo are at least engaged in a limited amount of activity. On the other hand, among sufficiently active people, those living in Pelotas are more active.